POSISI DUDUK DAN NYERI PUNGGUNG BAWAH PADA KARYAWAN KANTOR - Purnawinadi, I Gede; Sitanggang, Yohanes Binor (Klabat Journal of Nursing, 2022)
Low back pain is a symptom in the form of pain in the lumbosacral area (lower back) caused by various reasons, one of which is a sitting position, where the body weight rests on the buttocks by touching a horizontal object. A good sitting position if the back is straight, the head is not bent and the position of the thighs is parallel to the floor. The purpose of this study was to determine the relationship between sitting position and low back pain in employees. This research method uses descriptive analytic with a cross-sectional approach. The number of samples was calculated using the slovin formula as many as 52 respondents. The results of the study: the majority of employees (96.1%) are in a sitting position with a moderate to high level of risk. Then the most low back pain was in mild pain 46.2% (24 respondents). There is no significant relationship with the value 0.345 (p value > 0.05). The sitting position of employees has the largest percentage category, which is moderate risk and the largest low back pain is mild pain. It is expected that employees will pay attention to their sitting position while working and can rest or stretch their muscles between work hours in order to get optimal work results. Keywords: employees, low back pain, sitting position. Nyeri punggung bawah merupakan suatu gejala berupa rasa nyeri di daerah lumbosakral (punggung bawah) yang ditimbulkan oleh berbagai sebab, salah satunya adalah posisi duduk, dimana berat badan bertumpu pada bokong dengan bersentuhan pada suatu benda yang horizontal. Posisi duduk yang baik apabila punggung tegak lurus, kepala tidak menunduk dan posisi paha sejajar dengan lantai. Tujuan penelitian ini adalah untuk mengetahui hubungan antara posisi duduk dengan nyeri punggung bawah pada karyawan. Metode penelitian ini menggunakan deskriptif analitik dengan pendekatan cross-sectional. Jumlah sampel dihitung menggunakan rumus slovin sebanyak 52 responden. Hasil penelitian: mayoritas karyawan (96,1%) berada pada posisi duduk dengan tingkat resiko sedang hingga tinggi. Kemudian nyeri punggung bawah terbanyak berada pada nyeri ringan 46,2% (24 responden). Tidak ada hubungan yang signifikan dengan nilai 0,345 (p value > 0,05). Posisi duduk karyawan memiliki kategori persentase terbesar ialah risiko sedang dan nyeri punggung bawah terbesar ialah nyeri ringan. Diharapkan karyawan untuk tetap memperhatikan posisi duduk pada saat berkerja dan dapat istirahat atau peregangan otot disela waktu kerja agar mendapat hasil pekerjaan yang optimal. Kata Kunci: karyawan, nyeri punggung bawah, posisi duduk.